2-[(4-Hydroxybenzyl) Amino] Phenol (HBAP) Restores the Mutated p53 to the Level Similar to That of Wild-Type p53 Protein and Inhibits Breast Cancer Growth in vivo to by Inducing Tumor Cells Apoptosis - Xu, Chenxi; Zhuang, Jianjian; Zhang, Xiaobo (Frontiers in Cell and Developmental Biology, 2020)
P53 is a transcriptional factor that plays important roles in apoptosis and is mutated in more than 50% of tumor cells. However, the restoration of mutated p53 to the level similar to wild-type p53 by a natural compound has not been explored intensively. In this study, the 2-[(4-hydroxybenzyl) amino] phenol (HBAP) compound, obtained from deep-sea virus-challenged thermophile Geobacillus sp. E263, interacted specifically with the mutated p53 protein. HBAP was able to induce apoptosis of p53-mutated breast cancer cells, but not normal breast cells and p53-unmutated breast cancer cells. HBAP activated the mutant p53 transcriptional activity by restoring the function of mutant p53 to that of wild-type p53. Further analysis indicated that HBAP bound only to the DNA binding domain of mutant p53 and that the interaction was dependent on the HBAP hydroxyl groups. In vivo data demonstrated that HBAP was toxicity-free and could suppress tumor growth by inducing tumor cell apoptosis. Therefore our findings revealed that recovering mutated p53 function to that of wild-type p53 caused by HBAP triggered cancer cell apoptosis and that metabolites from deep-sea virus-challenged thermophiles could be a promising source of anti-tumor drugs.